The Teaching of Roman Law at the University of Mexico - Morineau, Marta (1986)
This article addresses the teaching of Roman Law at the University of Mexico, highlighting its relevance throughout the nineteenth and twentieth centuries. During the colonial period, this discipline was the mainstay of legal education at the university, following the model of European universities. Later, after independence, Patriotic Law started to gain prominence, although Roman Law continued to be essential. However, in 1907 it was eliminated from the compulsory curriculum, being limited to specialties. Then, in 1913, it was reintroduced as a required subject due to its importance for the formation of solid legal criteria. In the twentieth century, multiple modifications were made, being relevant the reform of 1922, which replaced the Roman Law courses by four courses of History of Law, although the first continued to be the basis of the historical legal study. Finally, the author concludes that the teaching of Roman Law, although subject to curricular changes, has always played a crucial role in the training of Mexican lawyers, despite fluctuations in its obligatory nature and the depth of its study.